Business strategy formulation for â€œexpat helper indonesiaâ€ in order to increase market growth and develop a sustainable competitive advantage - Dhiani Rakhmawati, Meita; Hamsal, Mohammad (The Indonesian Journal of Business Administration, 2016)
Abstract – Expat Helper Indonesia, an Indonesian company providing one-stop domestic services for expatriates in Indonesia, is facing some issues in running its business. That gaps are then affected the company’s revenues. Current more competitive business competition is also such an inevitable threat for the company. For that reasons, Expat Helper Indonesia needs to find suitable strategy to increase its market growth in order to generate more revenues, and develop a sustainable competitive advantage in order to survive in business competition. To support the research analysis, relevant data and information are gathered in qualitative method; through interview, observation, and literature review. The research started by analyzing the company’s external and internal environment to explore more its strengths, weaknesses, opportunities, and threats. The internal resource-based analysis indicates that Expat Helper Indonesia’s level of competitiveness is still in temporary competitive advantage. The proposed business-level strategy suggests that the company needs to remain in focused-differentiation strategy, considering its initial branding and the nature of the market segments. The analysis is also resulting four sets of strategic alternatives, in which together with all the output of strategy formulation, will be demonstrated in a new proposed business model canvas and implementation plan. Some dominant additions in proposed business model canvas are in marketing activities, customer relationship, channels, and value propositions. Keywords: business strategy, business canvas, market growth, sustainable competitive advantage